2021
DOI: 10.3390/su13052440
|View full text |Cite
|
Sign up to set email alerts
|

Who Wants Chicken? Uncovering Consumer Preferences for Produce of Alternative Chicken Product Methods

Abstract: As ethical and environmental concerns regarding current poultry production systems arise, consumers look for alternatives. This study assesses consumers’ preferences for chicken meat of dual-purpose breeds (DPBs), regionally produced feedstuff, and specific breeds, along with attitudes and social norms that explain these preferences. We conducted an online survey (n = 934) including a discrete choice experiment and elements of the theory of planned behavior. Results show that after price, product and feedstuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Although feather pecking occurs to a lesser extent during rearing than during the laying period, the plumage condition during rearing is a crucial factor to ensure intact plumage during the laying period (Janczak & Riber, 2015). Since improved animal welfare seems to be necessary in the marketing of products using regional breeds (Escobedo del Bosque et al., 2021), plumage condition that is readily visible to consumers is of particular interest. In the present study, which showed generally good integument condition, plumage damage and skin lesions were most pronounced at days 35, 53 and 105 of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although feather pecking occurs to a lesser extent during rearing than during the laying period, the plumage condition during rearing is a crucial factor to ensure intact plumage during the laying period (Janczak & Riber, 2015). Since improved animal welfare seems to be necessary in the marketing of products using regional breeds (Escobedo del Bosque et al., 2021), plumage condition that is readily visible to consumers is of particular interest. In the present study, which showed generally good integument condition, plumage damage and skin lesions were most pronounced at days 35, 53 and 105 of age.…”
Section: Discussionmentioning
confidence: 99%
“…(Escobedo del Bosque et al, 2021), plumage condition that is readily visible to consumers is of particular interest. In the present study, which showed generally good integument condition, plumage damage and skin lesions were most pronounced at days 35, 53 and 105 of age.…”
mentioning
confidence: 99%
“…An important advantage of chicken meat compared to other types of meat is certainly the fact that it is accepted by all cultures and religions [7], while the relatively low price of chicken meat [35] compared to beef, lamb, and pork provides the opportunity to use this highly valuable food in everyday diets [36,37].…”
Section: Importance Of Poultry Meat In Human Nutritionmentioning
confidence: 99%
“…Consumers buying decisions for chicken meat are impacted by several aspects, depending on the information available. Price is certainly among the most important attributes when making buying decisions for meat (Clark et al, 2017;Escobedo del Bosque et al, 2021) but animal welfare attributes are of importance, too. Increased willingness-to-pay for broiler chicken with higher welfare levels is generally given but is lower compared to other animal products such as dairy (Clark et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…People with higher levels of animal welfare concerns have found to eat less animal products and to pay more attention to welfare labels when buying animal products (Clark et al, 2016). Feed and product origin also influence buying decisions in broiler chicken and are of higher importance compared to breeds (Escobedo del Bosque et al, 2021).…”
Section: Introductionmentioning
confidence: 99%